Walking with Neuropathic Pain: Paradoxical Shift from Burden to Support? - David J. Kopsky; Jan M. Keppel Hesselink; Roberto Casale (Case Reports in Medicine)
Baclofen 5% cream can be used for the treatment of neuropathic pain. We describe an unusual case of a neuropathic pain patient with spinal cord injury. A 71-year-old woman with a partial spinal cord injury lesion at L4 complained of tingling, pins and needles, and burning in her legs. She scored her pain as 6 before adding baclofen 5% cream to her pain medication (pregabalin 450 mg, acetaminophen 3000 mg, and diclofenac 150 mg daily). One month later she experienced complete pain relief, though experienced increased difficulties in walking, leading to frequent falls. Her steadier walking without stumbling and falling was more important to her than pain reduction. Thus she decided to stop using baclofen. This unusual case report discusses two important issues that relate to pain medicine and rehabilitation in patients with painful spinal cord lesions: (1) the presence of wide areas of sensory loss “covered” by the presence of painful sensations and (2) pathological sensations that can be used and integrated in the body schema to create an improved spatiovisual orientation and thus mobility. Both these aspects have to be taken into account when treating pain and design rehabilitation programs.